2018
DOI: 10.1055/a-0605-3857
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Determination of Phenolic Glycosides and Anthraquinones from Rhizomes of Various Reynoutria Species

Abstract: Giant knotweeds of the genus (syn.)-, and a hybrid of them, -are noxious invasive plants in Europe and North America. is a traditional East Asian (Japan and China) drug (). Recently, it has been included in European Pharmacopoeia as one of the traditional Chinese medicinal herbs. In this study, a reversed-phase high performance liquid chromatography method with diode array detector and time-of-flight mass spectrometry was developed and validated for the profiling of rhizomes from European invasive populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 20 publications
(61 reference statements)
4
53
0
1
Order By: Relevance
“…Compounds 44 and 60 has been previously reported in studied species by using HR-MS analysis [5] and japonica [11]. In our study, compound 78 was observed also in R. bohemica.…”
Section: Anthraquinonessupporting
confidence: 83%
See 2 more Smart Citations
“…Compounds 44 and 60 has been previously reported in studied species by using HR-MS analysis [5] and japonica [11]. In our study, compound 78 was observed also in R. bohemica.…”
Section: Anthraquinonessupporting
confidence: 83%
“…R. sachalinensis contains significantly less anthraquinones and no stilbenes but the highest amount of phenylpropanoidderived disaccharide esters than R. japonica. The phytochemical profile of R. x bohemica was intermediate between the two parent species [5]. Some of the therapeutic effects of studied species are likely to be influenced by their antioxidant properties and this in turn is frequently associated with a high stilbene content [6].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recently, we tentatively identified flavan-3-ols and B-type proanthocyanidins from monomers up to decamers (monomers-flavan-3-ols, dimers, trimers, tetramers, pentamers, hexamers, heptamers, octamers, nonamers and decamers) and some of their gallates (monomer gallates, dimer gallate, dimer digallates, trimer gallates, tetramer gallates, pentamer gallates, hexamer gallates) in Japanese knotweed rhizomes [12,13]. Other authors reported identification of monomers [8,9,[14][15][16], monomer gallates [8,14,16], dimers [8,9,15], dimer gallates [15,16] dimer digallates [15,16] trimers [15], trimer gallates [15] trimer digallates [15] tetramer [15], tetramer gallates [15], pentamers [15], heptamers [15] and octamers [15] in rhizomes of Japanese [8,9,[14][15][16], Bohemian [14,15] and giant knotweed [8,9,[14][15][16]. However, only monomers [8,9], monomer gallates [8,9], dimers [8,9], dimer gallates [8,…”
Section: Introductionmentioning
confidence: 99%
“…It is used traditionally as an herbal medicine in its natural distribution area for the treatment of arthralgia, jaundice, amenorrhea, cough, scalds and burns, traumatic injuries, carbuncles and sores [ 10 ]. Our earlier study showed that rhizomes of R. sachalinensis are a rich source of phenylpropanoid disaccharide esters with a predominant amount of vanicoside B [ 11 , 12 , 13 ]. The cytotoxicity of vanicosides A and B against melanoma cell lines has not been studied so far, but the cytotoxicity of other compounds belonging to disaccharide esters of phenylpropanoids was reported against different cancer cell lines [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%